Challenges and contradictions of contemporary educated muslim women - Khan, Mariya Seemin (Kulliyyah of Education, International Islamic University Malaysia, 2016)
The purpose of the study is to understand the notion of what is to be an educated Muslim woman in today's society -- as understood and defined by the participants themselves. Furthermore is examined the set of challenges and contradictions that are experiences unique to these educated Muslim women. The research draws upon the lived experiences of seven educated Muslim women professionals through in-depth interviews conducted in order to catch a glimpse into their private lives. This study makes an attempt to deconstruct these lived experiences of the Muslim women and to analyze the daily dilemmas and problems they face on a daily basis. It also explores the coping strategies employed by these women in dealing with the challenges and the contradictions, also the role of education, the family and the society in perpetuating these challenges and contradiction. After setting the background and the theoretical and philosophical parameters in the first three chapters, the final chapters narrate the stories of these seven educated Muslim women. These stories are subsequently thematically analyzed and an analysis of each question is given. This study shows that though Islam has ceded women a high status, this has not been properly translated into practice. Educated Muslim women are struggling with double duty, lack of support system, feelings of guilt, the ambiguity and unpredictability of the home duties and affairs, unrealistic expectations in balancing between home and career, the superficial and self-serving of the Muslim public discourse.